The Madwoman in the Attic : the Woman Writer and the Nineteenth-Century Literary Imagination - Gilbert, Sandra M.; Gubar, Susan (Veritas Paperbacks Ser., 2020)
"A feminist classic."--Judith Shulevitz, New York Times Book Review"A pivotal book, one of those after which we will never think the same again."--Carolyn G. Heilbrun, Washington Post Book World A pathbreaking book of literary criticism is now reissued with a new introduction by Lisa Appignanesi that speaks to how The Madwoman in the Attic set the groundwork for subsequent generations of scholars writing about women writers, and why the book still feels fresh some four decades later.